The Role of the Millennial Generation in the Creativity of the Anti-Money Politics Movement (Journal of Creativity Student, 2022)
Indonesia in its government system uses democracy, which means that it upholds human rights. Especially about the election of their representatives in government. In this election of representatives, the people are given the right to vote to elect their representatives in running the government of the State of Indonesia. However, in practice there are several obstacles and even violations, for example money politics. These violations have undermined the value of the general election. However, there is a group in the general election that has a big role, namely millennials. Because of this, it is necessary to examine the legal polemic regarding money politics and how millennials can come to take part. The method used is normative juridical. The result is that the law in Indonesia has included regulations regarding money politics. However, in terms of implementing sanctions, it is still less than law enforcers, therefore this position can be filled by millennials. And millennials can also carry out fair and honest elections.